Possibilities of Applying Multimedia Technologies in Inclusive Education - Žalytė-Linkuvienė, Simona (Jaunųjų mokslininkų darbai, 2021)
Rapidly changing social, economic and cultural environment, the development of digital technologies, the global pandemic that broke out in 2020 and demographic challenges increase society’s need for constant change and improvement. Against the background of these challenges, the need to provide every member of society with equal opportunities for development is emphasized. This is an essential principle of inclusive education. Global and national documents emphasizing the need for inclusive education call for strengthening the ability of education to connect with all learners with behavioral, psychological, physiological or special abilities, regardless of nationality, social status, emphasis on respect for, access to and care for educational diversity, its change and growth. Inclusive education is best defined by the principles of the Good School Characteristics. Therefore, in this work, inclusive education is understood as an educational process characterized by the principles of the Good School Concept. As in all areas of our lives, the successful implementation of the educational process is undoubtedly influenced by digital multimedia technologies. There are often questions about the coherence between the technologies chosen and the process. Therefore, the possibilities of applying of multimedia technologies with inclusive education were chosen as the object of the article. The aim of the research is to evaluate the research areas of researchers analyzing the possibilities of multimedia technologies on the basis of the analysis of scientific literature, which are in line with the essential principles of inclusive education. The study concludes that the quality and values of educators’ competencies become particularly important in inclusive settings, but that there is a lack of formal research that has a direct impact on students’ achievements, social and emotional well-being and personal development. Multimedia technologies can be a great tool to achieve the goals of inclusive education; the attention of researchers working with technologies related to multimedia (sound, image, computer graphics, interactivity of the mentioned media) to pedagogical goals is particularly poor.